The association between body mass index and health literacy in high school Students: A cross-sectional study - Mohammad Reza Zare-Zardiny; Faroukh Abazari; Mohammad Ali Zakeri; Majid Dastras; Jamileh Farokhzadian (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Obesity and overweight in children and adolescents have become a global problem in recent years. Adolescence increases the likelihood of obesity in adulthood and associated illnesses. Nowadays, health literacy is one of the greatest determinants of the health. This study was conducted to evaluate the correlation between body mass index (BMI) and health literacy in high school students. MATERIALS AND METHODS: In this descriptive-analytical study, 430 high school students were enrolled in a multi-stage random method in Yazd city in the center of Iran. The data were collected through The Health Literacy Measure for Adolescents and calculate BMI with measurement of height and weight of adolescents. The data were then analyzed using SPSS 25 and descriptive and inferential statistics (Chi-square and multivariate regression). RESULTS: The results showed that the mean score of BMI (21.76 ± 3.76) was in a normal range. The score of health literacy was at the borderline level (58.44 ± 13.79). BMI was not significantly correlated with health literacy (P = 0.09). BMI was significantly different in terms of age, high school grade, school type, and health status. School type and health status predict 37% of the variance of BMI (R2 = 37%) and the best predictor was health status (P < 0.05). CONCLUSIONS: The results of the present study showed that BMI was not correlated with health literacy and student health literacy was at the borderline level. It is necessary to carry out further studies on the causes and facilitators and the barriers to increasing health literacy. Furthermore, educational interventions are needed to prevent the increase of BMI in adolescents and identify determining factors.